2020
DOI: 10.1111/eci.13314
|View full text |Cite
|
Sign up to set email alerts
|

High mortality in COVID‐19 patients with mild respiratory disease

Abstract: Introduction:Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has infected 189 000 people in Italy, with more than 25 000 deaths. Several predictive factors of mortality have been identified; however, none has been validated in patients presenting with mild disease. Methods: Patients with a diagnosis of interstitial pneumonia caused by SARS-CoV-2, presenting with mild symptoms, and requiring hospitalization in a nonintensive care unit with known discharge status were prospectively collected and ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 27 publications
4
37
1
3
Order By: Relevance
“…The majority of deaths occurred in patients over age 60 (60.8%). There was a clear increase in the risk of mortality among older patients which is consistent with current COVID-19 literature for adults [5-9, 12, 13, 15, 21,22]. Suleyman et al reported the odds of death in patients over 60 were 5.3 times that of patients less than 60 years (p < 0.001) [6].…”
Section: Discussionsupporting
confidence: 79%
“…The majority of deaths occurred in patients over age 60 (60.8%). There was a clear increase in the risk of mortality among older patients which is consistent with current COVID-19 literature for adults [5-9, 12, 13, 15, 21,22]. Suleyman et al reported the odds of death in patients over 60 were 5.3 times that of patients less than 60 years (p < 0.001) [6].…”
Section: Discussionsupporting
confidence: 79%
“…Twenty-two studies [ 20 , 26 , 74 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 102 ] showed higher D-Dimer levels in 1149 subjects dead with COVID-19 as compared to 4407 subjects survived to COVID-19 (SMD: 3.88; 95%CI: 2.70, 5.07, p < 0.001, Figure 3 ). The heterogeneity among studies was significant (I 2 : 99.4%, p < 0.001) and was not reduced by the exclusion of one study at a time.…”
Section: Resultsmentioning
confidence: 99%
“…A lower PLT count (SMD: −0.60, 95%CI: −0.82, −0.38; p < 0.001, Figure 4 ) was found in 1339 non-survivors to COVID-19 as compared to 5637 survivors enrolled in 21 studies [ 20 , 22 , 26 , 74 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 91 , 92 , 93 , 94 , 95 , 97 , 98 , 100 , 101 , 102 ]. The heterogeneity among studies was significant (I 2 : 90.3%, p < 0.001) and was not reduced by the exclusion of one study at a time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research was pooled from 14 geographies with China the most commonly reported (n = 43) [19,, followed by USA (n = 15) [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82], Italy (n = 4) [83][84][85][86], and UK (N = 3) [87][88][89]. The remaining papers were from Mexico [90,91], South Korea [92,93], Turkey [94], Brazil [95], Denmark [96], France [97], Israel [98], Iran [99], and Poland [100].…”
Section: Plos Onementioning
confidence: 99%